Noninvasive markers for esophageal varices in children with cirrhosis - Parisa Rahmani; Fatemeh Farahmand; Ghobad Heidari; Azadeh Sayarifard (The Korean Pediatric Society, 2021)
Background The diagnosis of esophageal varices (EV) is based on the findings of esophagogastroduodenoscopy (EGD), biopsy, and serum markers. Thus, noninvasive cost-effective tests through which high-risk EV children can be diagnosed are needed. Purpose This cross-sectional study aimed to identify the noninvasive markers for EV in children with liver cirrhosis. Methods A total of 98 children with liver cirrhosis were evaluated in this study. The spleen size, platelet count, serum albumin, liver function test results, and risk scores were evaluated prior to endoscopy. The endoscopic investigations aimed to identify the presence of EV and red signs, and determine varices sizes. Results Endoscopy revealed varices in 43 subjects (43.9%). The spleen size, platelet count, international normalized ratio, aspartate aminotransferase to platelet ratio index (APRI), platelet count to spleen size ratio, and risk score differed significantly between patients with and without EV on univariate analysis; however, the logistic regression analysis showed no differences, indicating that none of these parameters were independently associated with the presence of EV. Conclusion Platelet count, risk score, platelet count to spleen size, and APRI can be useful tools for the identification of high-risk patients with EV and might reduce the need for invasive methods like EGD.